Aprotinin prevents proteolytic epithelial sodium channel (ENaC) activation and volume retention in nephrotic syndrome - Bohnert, Bernhard N.; Menacher, Martina; Janessa, Andrea; Woern, Matthias; Schork, Anja; Daiminger, Sophie; Kalbacher, Hubert; Haering, Hans-Ulrich; Daniel, Christoph; Amann, Kerstin Ute; Sure, Florian; Bertog, Marko; et al. (Kidney International, 2018)
Volume retention in nephrotic syndrome has been linked to activation of the epithelial sodium channel (ENaC) by proteolysis of its ?-subunit following urinary excretion of serine proteases such as plasmin. Here we tested whether pharmacological inhibition of urinary serine protease activity might protect from ENaC activation and volume retention in nephrotic syndrome. Urine from both nephrotic mice (induced by doxorubicin injection) and nephrotic patients exhibited high aprotinin-sensitive serine protease activity. Treatment of nephrotic mice with the serine protease inhibitor aprotinin by means of subcutaneous sustained-release pellets normalized urinary serine protease activity and prevented sodium retention, as did treatment with the ENaC inhibitor amiloride. In the kidney cortex from nephrotic mice, immunofluorescence revealed increased apical ?-ENaC staining, normalized by aprotinin treatment. In Xenopus laevis oocytes heterologously expressing murine ENaC, aprotinin had no direct inhibitory effect on channel activity but prevented proteolytic channel activation. Thus, our study shows that volume retention in experimental nephrotic syndrome is related to proteolytic ENaC activation by proteasuria and can be prevented by treatment with aprotinin. Hence, inhibition of urinary serine protease activity might become a therapeutic approach to treat patients with nephrotic-range proteinuri
EVALuna2:25560

Bile acids inhibit human purinergic receptor P2X4 in a heterologous expression system - Ilyaskin, Alexandr; Sure, Florian; Nesterov, Viatcheslav; Härteis, Silke; Korbmacher, Christoph (Journal of General Physiology, 2019)
We recently demonstrated that bile acids, especially tauro-deoxycholic acid (t-DCA), modify the function of the acid-sensing ion channel ASIC1a and other members of the epithelial sodium channel (ENaC)/degenerin (DEG) ion channel family. Surprisingly, ASIC1 shares a high degree of structural similarity with the purinergic receptor P2X4, a nonselective cation channel transiently activated by ATP. P2X4 is abundantly expressed in the apical membrane of bile duct epithelial cells and is therefore exposed to bile acids under physiological conditions. Here, we hypothesize that P2X4 may also be modulated by bile acids and investigate whether t-DCA and other common bile acids affect human P2X4 heterologously expressed in Xenopus laevis oocytes. We find that application of either t-DCA or unconjugated deoxycholic acid (DCA; 250 µM) causes a strong reduction (∼70%) of ATP-activated P2X4-mediated whole-cell currents. The inhibitory effect of 250 µM tauro-chenodeoxycholic acid is less pronounced (∼30%), and 250 µM chenodeoxycholic acid, cholic acid, or tauro-cholic acid did not significantly alter P2X4-mediated currents. t-DCA inhibits P2X4 in a concentration-dependent manner by reducing the efficacy of ATP without significantly changing its affinity. Single-channel patch-clamp recordings provide evidence that t-DCA inhibits P2X4 by stabilizing the channel's closed state. Using site-directed mutagenesis, we identifiy several amino acid residues within the transmembrane domains of P2X4 that are critically involved in mediating the inhibitory effect of t-DCA on P2X4. Importantly, a W46A mutation converts the inhibitory effect of t-DCA into a stimulatory effect. We conclude that t-DCA directly interacts with P2X4 and decreases ATP-activated P2X4 currents by stabilizing the closed conformation of the channel.
CRIS-Team Scopus Importer:2019-06-21

Disease-associated missense mutations in the pore loop of polycystin-2 alter its ion channel function in a heterologous expression system - Staudner, Tobias; Geiges, Linda; Khamseekaew, Juthamas; Sure, Florian; Korbmacher, Christoph; Ilyaskin, Alexandr (Journal of Biological Chemistry, 2024)
Polycystin-2 (PC2) is mutated in ∼15% of patients with autosomal dominant polycystic kidney disease (ADPKD). PC2 belongs to the family of transient receptor potential (TRP) channels and can function as a homotetramer. We investigated whether three disease-associated mutations (F629S, C632R, or R638C) localized in the channel's pore loop alter ion channel properties of human PC2 expressed in Xenopus laevis oocytes. Expression of wild-type (WT) PC2 typically resulted in small but measurable Na+ inward currents in the absence of extracellular divalent cations. These currents were no longer observed when individual pore mutations were introduced in WT PC2. Similarly, Na+ inward currents mediated by the F604P gain-of-function (GOF) PC2 construct (PC2 F604P) were abolished by each of the three pore mutations. In contrast, when the mutations were introduced in another GOF construct, PC2 L677A N681A, only C632R had a complete loss-of-function effect, whereas significant residual Na+ inward currents were observed with F629S (∼15%) and R638C (∼30%). Importantly, the R638C mutation also abolished the Ca2+ permeability of PC2 L677A N681A and altered its monovalent cation selectivity. To elucidate the molecular mechanisms by which the R638C mutation affects channel function, molecular dynamics (MD) simulations were used in combination with functional experiments and site-directed mutagenesis. Our findings suggest that R638C stabilizes ionic interactions between Na+ ions and the selectivity filter residue D643. This probably explains the reduced monovalent cation conductance of the mutant channel. In summary, our data support the concept that altered ion channel properties of PC2 contribute to the pathogenesis of ADPKD.
CRIS-Team Scopus Importer:2024-08-09
Keywords: autosomal dominant polycystic kidney disease (ADPKD); electrophysiology; molecular dynamics; oocyte; polycystin; renal physiology; site-directed mutagenesis; transient receptor potential channels (TRP channels); two electrode voltage clamp; Xenopus

Proteolytic activation of the epithelial sodium channel (ENaC) by factor VII activating protease (FSAP) and its relevance for sodium retention in nephrotic mice - Artunc, Ferruh; Bohnert, Bernhard N.; Schneider, Jonas C.; Staudner, Tobias; Sure, Florian; Ilyaskin, Alexandr; Worn, Matthias; Essigke, Daniel; Janessa, Andrea; Nielsen, Nis V.; Birkenfeld, Andreas L.; Etscheid, Michael; et al. (Pflügers Archiv: European Journal of Physiology, 2021)
Proteolytic activation of the epithelial sodium channel (ENaC) by aberrantly filtered serine proteases is thought to contribute to renal sodium retention in nephrotic syndrome. However, the identity of the responsible proteases remains elusive. This study evaluated factor VII activating protease (FSAP) as a candidate in this context. We analyzed FSAP in the urine of patients with nephrotic syndrome and nephrotic mice and investigated its ability to activate human ENaC expressed in Xenopus laevis oocytes. Moreover, we studied sodium retention in FSAP-deficient mice (Habp2−/−) with experimental nephrotic syndrome induced by doxorubicin. In urine samples from nephrotic humans, high concentrations of FSAP were detected both as zymogen and in its active state. Recombinant serine protease domain of FSAP stimulated ENaC-mediated whole-cell currents in a time- and concentration-dependent manner. Mutating the putative prostasin cleavage site in γ-ENaC (γRKRK178AAAA) prevented channel stimulation by the serine protease domain of FSAP. In a mouse model for nephrotic syndrome, active FSAP was present in nephrotic urine of Habp2+/+ but not of Habp2−/− mice. However, Habp2−/− mice were not protected from sodium retention compared to nephrotic Habp2+/+ mice. Western blot analysis revealed that in nephrotic Habp2−/− mice, proteolytic cleavage of α- and γ-ENaC was similar to that in nephrotic Habp2+/+ animals. In conclusion, active FSAP is excreted in the urine of nephrotic patients and mice and activates ENaC in vitro involving the putative prostasin cleavage site of γ-ENaC. However, endogenous FSAP is not essential for sodium retention in nephrotic mice.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Epithelial sodium channel (ENaC); Factor VII activating protease; FSAP-HABP2; Nephrotic syndrome; Serine protease

The small molecule activator S3969 stimulates the epithelial sodium channel by interacting with a specific binding pocket in the channel's β-subunit - Sure, Florian; Einsiedel, Jürgen; Gmeiner, Peter; Duchstein, Patrick; Zahn, Dirk; Korbmacher, Christoph; Ilyaskin, Alexandr (Journal of Biological Chemistry, 2024)
The epithelial sodium channel (ENaC) is essential for mediating sodium absorption in several epithelia. Its impaired function leads to severe disorders, including pseudohypoaldosteronism type 1 and respiratory distress. Therefore, pharmacological ENaC activators have potential therapeutic implications. Previously, a small molecule ENaC activator (S3969) was developed. So far, little is known about molecular mechanisms involved in S3969-mediated ENaC stimulation. Here, we identified an S3969-binding site in human ENaC by combining structure-based simulations with molecular biological methods and electrophysiological measurements of ENaC heterologously expressed in Xenopus laevis oocytes. We confirmed a previous observation that the extracellular loop of β-ENaC is essential for ENaC stimulation by S3969. Molecular dynamics simulations predicted critical residues in the thumb domain of β-ENaC (Arg388, Phe391, and Tyr406) that coordinate S3969 within a binding site localized at the β-γ-subunit interface. Importantly, mutating each of these residues reduced (R388H; R388A) or nearly abolished (F391G; Y406A) the S3969-mediated ENaC activation. Molecular dynamics simulations also suggested that S3969-mediated ENaC stimulation involved a movement of the α5 helix of the thumb domain of β-ENaC away from the palm domain of γ-ENaC. Consistent with this, the introduction of two cysteine residues (βR437C – γS298C) to form a disulfide bridge connecting these two domains prevented ENaC stimulation by S3969 unless the disulfide bond was reduced by DTT. Finally, we demonstrated that S3969 stimulated ENaC endogenously expressed in cultured human airway epithelial cells (H441). These new findings may lead to novel (patho-)physiological and therapeutic concepts for disorders associated with altered ENaC function.
CRIS-Team Scopus Importer:2024-03-29
Keywords: electrophysiology; epithelial sodium channel (ENaC); H441 cell line; molecular docking; molecular dynamics; oocyte; S3969; site-directed mutagenesis; small molecule activator; two electrode voltage clamp

Transmembrane Serine Protease 2 and Proteolytic Activation of the Epithelial Sodium Channel in Mouse Kidney - Sure, Florian; Afonso, Sara; Essigke, Daniel; Schmidt, Paul; Kalo, M. Zaher; Nesterov, Viatcheslav; Kißler, Alicia; Bertog, Marko; Rinke, Ralf; Wittmann, Sabine; Broeker, Katharina A.E.; Gramberg, Thomas; et al. (Journal of the American Society of Nephrology, 2024)
Background The renal epithelial sodium channel (ENaC) is essential for sodium balance and blood pressure control. ENaC undergoes complex proteolytic activation by not yet clearly identified tubular proteases. Here, we examined a potential role of transmembrane serine protease 2 (TMPRSS2). Methods Murine ENaC and TMPRSS2 were (co-)expressed in Xenopus laevis oocytes. ENaC cleavage and function were studied in TMPRSS2-deficient murine cortical collecting duct (mCCDcl1) cells and TMPRSS2-knockout (Tmprss2−/−) mice. Short-circuit currents (ISC) were measured to assess ENaC-mediated transepithelial sodium transport of mCCDcl1 cells. The mCCDcl1 cell transcriptome was studied using RNA sequencing. The effect of low-sodium diet with or without high potassium were compared in Tmprss2−/− and wildtype mice using metabolic cages. ENaC-mediated whole-cell currents were recorded from microdissected tubules of Tmprss2−/− and wildtype mice. Results In oocytes, co-expression of murine TMPRSS2 and ENaC resulted in fully cleaved γ-ENaC and 2-fold stimulation of ENaC currents. High baseline expression of TMPRSS2 was detected in mCCDcl1 cells without a stimulatory effect of aldosterone on its function or transcription. TMPRSS2 knockout in mCCDcl1 cells compromised γ-ENaC cleavage and reduced baseline and aldosterone-stimulated ISC which could be rescued by chymotrypsin. A compensatory transcriptional upregulation of other proteases was not observed. Tmprss2−/− mice kept on standard diet exhibited no apparent phenotype, but renal γ-ENaC cleavage was altered. In response to a low-salt diet, particularly with high potassium intake, Tmprss2−/− mice increased plasma aldosterone significantly more than wildtype mice to achieve a similar reduction of renal sodium excretion. Importantly, the stimulatory effect of trypsin on renal tubular ENaC currents was much more pronounced in Tmprss2−/− mice than that in wildtype mice. This indicated the presence of incompletely cleaved and less active channels at the cell surface of TMPRSS2-deficient tubular epithelial cells. Conclusions TMPRSS2 contributes to proteolytic ENaC activation in mouse kidney in vivo.
CRIS-Team Scopus Importer:2024-11-08

Transmembrane serine protease 2 (TMPRSS2) is involved in proteolytic activation of the epithelial sodium channel (ENaC) in mouse cortical collecting duct (mCCDcl1) cells - Sure, Florian; Afonso, Sara; Bertog, Marko; Rinke, Ralf; Wittmann, Sabine; Gramberg, Thomas; Ilyaskin, Alexandr; Korbmacher, Christoph (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Transmembrane serine protease 2 (TMPRSS2) proteolytically activates the epithelial sodium channel (ENaC) by cleaving the channel's gamma-subunit - Sure, Florian; Bertog, Marko; Afonso, Sara; Diakov, A.; Rinke, Ralf; Madej, M. G.; Wittmann, Sabine; Gramberg, Thomas; Korbmacher, Christoph; Ilyaskin, Alexandr (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Transmembrane serine protease 2 (TMPRSS2) proteolytically activates the epithelial sodium channel (ENaC) by cleaving the channel's gamma-subunit - Sure, Florian; Bertog, Marko; Afonso, Sara; Diakov, Alexei; Rinke, Ralf; Madej, M. Gregor; Wittmann, Sabine; Gramberg, Thomas; Korbmacher, Christoph; Ilyaskin, Alexandr (Journal of Biological Chemistry, 2022)
The epithelial sodium channel (ENaC) is a heterotrimer consisting of alpha-, beta-, and gamma-subunits. Channel activation requires proteolytic release of inhibitory tracts from the extracellular domains of alpha-ENaC and gamma-ENaC; however, the proteases involved in the removal of the gamma-inhibitory tract remain unclear. In several epithelial tissues, ENaC is coexpressed with the transmembrane serine protease 2 (TMPRSS2). Here, we explored the effect of human TMPRSS2 on human alpha beta gamma-ENaC heterologously expressed in Xenopus laevis oocytes. We found that coexpression of TMPRSS2 stimulated ENaC-mediated whole-cell currents by approximately threefold, likely because of an increase in average channel open probability. Furthermore, TMPRSS2-dependent ENaC stimulation was not observed using a catalytically inactive TMPRSS2 mutant and was associated with fully cleaved gamma-ENaC in the intracellular and cell surface protein fractions. This stimulatory effect of TMPRSS2 on ENaC was partially preserved when inhibiting its proteolytic activity at the cell surface using aprotinin but was abolished when the gamma-inhibitory tract remained attached to its binding site following introduction of two cysteine residues (S155C-Q426C) to form a disulfide bridge. In addition, computer simulations and site-directed mutagenesis experiments indicated that TMPRSS2 can cleave gamma-ENaC at sites both proximal and distal to the gamma-inhibitory tract. This suggests a dual role of TMPRSS2 in the proteolytic release of the gamma-inhibitory tract. Finally, we demonstrated that TMPRSS2 knockdown in cultured human airway epithelial cells (H441) reduced baseline proteolytic activation of endogenously expressed ENaC. Thus, we conclude that TMPRSS2 is likely to contribute to proteolytic ENaC activation in epithelial tissues in vivo.
CRIS-Team WoS Importer:2022-06-24

Urokinase-type plasminogen activator (uPA) is not essential for epithelial sodium channel (ENaC)-mediated sodium retention in experimental nephrotic syndrome - Bohnert, Bernhard N.; Daiminger, Sophie; Woern, Matthias; Sure, Florian; Staudner, Tobias; Ilyaskin, Alexandr; Batbouta, Firas; Janessa, Andrea; Schneider, Jonas C.; Essigke, Daniel; Kanse, Sandip; Härteis, Silke; et al. (Acta Physiologica, 2019)
AIM: In nephrotic syndrome, aberrantly filtered plasminogen (plg) is converted to active plasmin by tubular urokinase-type plasminogen activator (uPA) and thought to lead to sodium retention by proteolytic activation of the epithelial sodium channel (ENaC). This concept predicts that uPA is an important factor for sodium retention and that inhibition of uPA might be protective in nephrotic syndrome. METHODS: Activation of amiloride-sensitive currents by uPA and plg were studied in Xenopus laevis oocytes expressing murine ENaC. In doxorubicin-induced nephrotic mice, uPA was inhibited pharmacologically by amiloride and genetically by the use of uPA-deficient mice (uPA-/- ). RESULTS: Experiments in Xenopus laevis oocytes expressing murine ENaC confirmed proteolytic ENaC activation by a combination of plg and uPA which stimulated amiloride-sensitive currents with concomitant cleavage of the ENaC γ-subunit at the cell surface. Treatment of nephrotic wild-type mice with amiloride inhibited urinary uPA activity, prevented urinary plasmin formation and sodium retention. In nephrotic mice lacking uPA (uPA-/- ), urinary plasmin formation from plg was suppressed and urinary uPA activity absent. However, in nephrotic uPA-/- mice, sodium retention was not reduced compared to nephrotic uPA+/+ mice. Amiloride prevented sodium retention in nephrotic uPA-/- mice which confirmed the critical role of ENaC in sodium retention. CONCLUSION: uPA is responsible for the conversion of aberrantly filtered plasminogen to plasmin in the tubular lumen in vivo. However, uPA-dependent plasmin generation is not essential for ENaC-mediated sodium retention in experimental nephrotic syndrome.
EVALuna2:208614